PENGEMBANGAN PRODUK PASCA PANEN (KERUPUK KEMPLANG IKAN LELE) SEBAGAI DIVERSIFIKASI OLAHAN PRODUK IKAN LELE DI DESA SUNGAI DUA KABUPATEN BANYUASIN - Rahul, Muhammad; Guttifera, Guttifera; Arafah, Elmeizy; Wulandari, Sri Wahyu; Wibowo, Prastiyo; Kanya, Maya Resta (Jurnal Abdi Insani, 2025)
Sungai Dua Village, located in Rambutan Subdistrict, Banyuasin Regency, South Sumatra, has significant potential for catfish farming due to its favorable geographical conditions. Catfish, known for its savory taste, is well-suited as a raw material for kemplang crackers. However, the local community lacks the knowledge and skills to process catfish into diversified products like kemplang crackers. The community engagement activity involved catfish farming groups, youth organizations, and the PKK women’s association in Sungai Dua Village, Rambutan Subdistrict, Banyuasin Regency. This activity aims to enhance the understanding and knowledge of Sungai Dua Village residents, especially PKK women, in developing post-harvest products. This is expected to increase community income and create new job opportunities. The implementation methods included activity coordination, training on post-harvest product development, mentoring, and monitoring. The first stage involved coordinating with the village authorities to identify the challenges faced by catfish farmers. Subsequently, training sessions were conducted on the nutritional benefits of catfish, product processing, the procedure for making kemplang crackers from catfish, and packaging strategies. A demonstration activity was then carried out by directly cooking kemplang crackers made from catfish harvested by farmers in Sungai Dua Village. Regular mentoring and monitoring were conducted weekly to observe the community’s progress in independently and sustainably producing catfish kemplang crackers. The activity demonstrated that the residents of Sungai Dua Village now understand and are knowledgeable about the process of developing post-harvest catfish products, specifically kemplang crackers. This has led to increased community income and the creation of new job opportunities.